PENGARUH LINGKUNGAN TERHADAP KEPUASAN KERJA DAN PRODUKTIVITAS KERJA KARYAWAN DI PT. MASUBA CITRA MANDIRI KABUPATEN ROKAN HULU PROVINSI RIAU - ,Nuryanti, Nosi Isnaeni , Zulfadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to analyze the influence of the work environment on satisfaction then the work environment on work productivity, the influence of work environment on productivity through job satisfaction and the effect of satisfaction on work productivity. The population in this study were 96 employees of PT Masuba Citra Mandiri Kabupaten Rokan Hulu Provinsi Riau. The sample in this study was 96 people. The data used in this study are primary data and secondary data, while data collection techniques use questionnaires. The data analysis technique used in this study is SEM, using SmartPLS software. The results of this study indicate that the work environment influence satisfaction. The work environment influence work productivity. Work environment influence work productivity through satisfaction. Satisfaction affects work productivity. Keywords: Work Environment, Team Cooperation, Satisfaction and Productivity